Molecular simulations of potential agents and targets of Alzheimer's disease - Joli, Luxolo (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Alzheimer's Disease (AD) is a neurodegenerative brain disorder that was first discovered in 1901 by Dr AloÃ¯s Alzheimer and was later reported publicly in 1906. The German doctor had a 51-yearold woman patient called Auguste Deter, who was suffering from a rare brain disorder with early signs of memory loss and cognition. Alzheimer's Disease is the most common type of dementia that affects people with the age of 65 years and older. There is no single known cause of Alzheimer's disease however, amyloid Î²-peptide (AÎ²1"“40/42) was found to be at the centre of AD pathogenesis and this connection was referred as "amyloid hypothesis" . It is suspected that an accumulation of amyloid Î²-peptide is a major contributor to neuronal dysfunction and degeneration. Alzheimer's disease is complex and therefore, currently there is no medication available that treats the disease. However, there are approaches that focus on helping people maintain mental function, manage behavioral symptoms, and slow down the symptoms of disease. According to South Africa's 2011 census, there are approximately 2.2 million people in South Africa with some form of dementia and therefore there is a need to find a treatment for the disease. This study aims to find agents and targets of Alzheimer's Disease by using different computational techniques such as molecular modelling. The study will use compounds from the South African Compounds Database (SANCDB) and the following therapeutic targets Î±-, Î²- and Î³-secretase, acetylcholinesterase, tau protein and neprilysin. A successful High-throughput Virtual Screening (HTVS) study to determine lead compounds was performed using a computational program called KNIME. Molecular docking was achieved with GLIDE as it allows for exhaustive ligand flexibility. The docking calculations were carried out using the high level of precision XP (extra precision) for enhanced docking accuracy. The binding affinities (docking scores) for the best bound ligands obtained from docking were in the order of -5 kcal/mol or less. The ligandSANC00370 was the best binding ligand against the protein 1J1C_B and had the best binding energy of -13.94 kcal/mol compared to others. The receptor-ligand complexes were analyzed using the interaction diagrams obtained from the Discovery Studio Visualizer and Maestro programs. Molecular Dynamics simulations were performed on the complexes obtained from docking to help in optimizing their interactions. The simulations were performed using the Desmond tool with the OPLS3 force field. 100 ns simulations were performed for six systems with the best docking score results epresenting each of the therapeutic targets and for the other complex systems, 50 ns simulations were performed. The Desmond simulations were analyzed using the Simulations Interaction Diagrams such as PL-RMSD, L-RMSF, P-RMSF, L-Torsions, P-SSE, LP-Contacts and L-Properties. Maestro was used to visualize the stability of the ligands in the active site during the simulation. All 13 Desmond simulations were successful however, there were 9 simulations which produced satisfactory results while the others were nsatisfactory. Based on the molecular docking and Molecular Dynamics results of this study, 9 potential targets and 6 potential agents were obtained successfully and can be studied further as therapeutics for Alzheimer's Disease.
Keywords: Alzheimer's disease -- Chemotherapy; Alzheimer's disease -- Treatment; Ligands (Biochemistry); Proteins -- Chemistry; Molecular dynamics -- Simulation methods